2016
DOI: 10.7754/clin.lab.2016.160209
|View full text |Cite
|
Sign up to set email alerts
|

Influential Factors of the Indeterminate Results Tested by QuantiFERON-TB Gold In-Tube (QFT-IT) Assay for Diagnosing TB Infection in HIV-Infected Patients

Abstract: The QFT-IT could be a potential, simple, and feasible method for diagnosing and screening TB in HIV-infected patients. In addition, the CD4 T-cell count, the lymphocyte count, and the lymphocyte percentage were influential factors of the indeterminate results of QFT-IT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, high SLEDAI scores seemed not related with a high proportion of indeterminate results, and this differs from some studies [20][21][22][23][24]. Other previous researches showed that CD4+ T cell count, lymphocyte count, and lymphocyte percentage were influencing factors for the indeterminate results of QFT-GIT in HIV and immunosuppressive people [25,26]. Glucocorticoid therapy is also another reason for the indeterminate outcome of QFT [20,27,28].…”
Section: Discussionmentioning
confidence: 89%
“…However, high SLEDAI scores seemed not related with a high proportion of indeterminate results, and this differs from some studies [20][21][22][23][24]. Other previous researches showed that CD4+ T cell count, lymphocyte count, and lymphocyte percentage were influencing factors for the indeterminate results of QFT-GIT in HIV and immunosuppressive people [25,26]. Glucocorticoid therapy is also another reason for the indeterminate outcome of QFT [20,27,28].…”
Section: Discussionmentioning
confidence: 89%
“…The rate of indeterminate results in the immunocompromised group was higher than that in the immunocompetent group in our study. The rate of indeterminate results was 7% in controls free from glucocorticoid and immunosuppressant treatment ( 28 ), but was up to 30% in patients with HIV and in those receiving high-dose corticosteroid therapy ( 29 , 30 ). Previous studies have found that lymphopenia, chronic renal disease, autoimmune disease, and chronic lung disease are independent predictive factors for indeterminate results from a QFT-GIT test ( 31 ).…”
Section: Discussionmentioning
confidence: 99%